CENTRALIZACIÓN POLÍTICA Y CONSTRUCCIÓN TERRITORIAL EN GUATEMALA. EL DEPARTAMENTO DE SANTA ROSA, 1840-1871 - Sarazúa Pérez, Juan Carlos (2007)
This article seeks to convey the main guidelines arising from the analysis of the territorial construction of the department of Santa Rosa, from 1852 to 1871. Its purpose is to interact with recent works on the construction of the nation during the Carrera period. Based on the methodology of regional history proposed by Arturo Taracena, this work aims to analyze the local elites in their multiple relationships with their Guatemalan counterparts and their impact on the political centralization after 1852. By focusing on a particular case, we are able to learn from the recent works on nationalism written by Douglas Sullivan-Gonzalez and on local history by Ann Jefferson, which have unwrapped new perspectives in the investigation of Eastern Guatemala.